Taylor's Cortical Dysplasia: A Confocal and Ultrastructural Immunohistochemical Study - Rita Garbelli; C. Munari; Silvia De Biasi; L. Vitellaro‐Zuccarello; Carlo Galli; Manuela Bramerio; Roberto Mai; Giorgio Battaglia; Roberto Spreafico (1999)
In the present report we describe the neuropathological characteristics of tissue surgically resected from three patients affected by intractable epilepsy secondary to cortical dysplasia. Common features, suggestive of a focal cortical dysplasia of Taylor, were observed in all specimens. Immunocytochemical procedures were performed using neuronal and glial markers and the sections were observed at light traditional and confocal microscopes. This part of the investigation pointed out: 1. cortical laminar disruption; 2. very large neurons displaying a pyramidal or round shape; 3. ballooned cells; 4. decrease of calcium binding proteins immunoreactivity; 5. abnormal nets of parvalbumin- and glutamic acid decarboxylase-positive puncta around giant neurons but not around ballooned cells. Ultrastructural investigation on the same material provided evidence of a high concentration of neurofilaments in giant neurons and of glial intermediate filaments in ballooned cells. In addition, immunolabeled GABAergic terminals clustered around giant neurons were not found to establish synapses on their cell bodies. The present data, derived from a limited sample of patients but showing very consistent features, suggest that in Taylor's type of cortical dysplasia a disturbance of migratory events could be paralleled by a disruption of cell differentiation and maturation and by an impairment of synaptogenesis. This latter mechanism seemed to affect especially the inhibitory elements, and could account for the hyperexcitability of this tissue and thus for the high epileptogenicity of Taylor's dysplasia.